Pomiędzy kolonializmem, imperializmem a globalizacją (Politeja, 2019)
Between Colonialism, Imperialism and Globalization The aim of the article is to share a view on today’s reality, it’s problems and threats from the prospect of colonialism and imperialism. The author seeks answers to the question to what extent, if any, colonialism and imperialism are still helpful to interpret the globalized world. In what manner shall we perceive the global reality as postcolonial and postimperial? The author attempts to prove that both imperialism and colonialism still have an impact on the postcolonial world.